Maternal short stature, household socio-economic status and stunting among under-two children attending an immunization clinic at a tertiary hospital in Kathmandu, Nepal (Nepal Medical College Journal, 2022)
Stunting or poor linear growth affects about 25% of children under five globally. Poor linear growth may occur due to lack of nutrients or due to hormonal influences. This study has investigated the relationship between maternal stature, household socio-economic status and linear growth among children below two years of age visiting the immunization clinic at an urban tertiary hospital in Kathmandu, Nepal. An observational cross-sectional analytical study was carried out through a face-to-face interview of mothers with a pretested standardized proforma. Anthropometric measurement of mother and child dyads was carried out to assess the nutritional status. Nutritional anthropometry tool in Epi-Info version 7.2.0.2 was used to calculate height-for-age z-scores (HAZ) based on the WHO 2007 reference data. A cut-off of –2 z-scores was used to define stunting (